2009
DOI: 10.1038/ismej.2009.10
|View full text |Cite
|
Sign up to set email alerts
|

The alkaline phosphatase PhoX is more widely distributed in marine bacteria than the classical PhoA

Abstract: Phosphorus (P) is a vital nutrient for all living organisms and may control the growth of bacteria in the ocean. Bacteria induce alkaline phosphatases when inorganic phosphate (Pi) is insufficient to meet their P-requirements, and therefore bulk alkaline phosphatase activity measurements have been used to assess the P-status of microbial assemblages. In this study, the molecular basis of marine bacterial phosphatases and their potential role in the environment were investigated. We found that only a limited nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
209
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(220 citation statements)
references
References 39 publications
8
209
1
2
Order By: Relevance
“…A recent study showed that PhoX is more abundant in the ocean than previously considered (18). We observed that PhoD is even more abundant than PhoX across a wide variety of marine habitats.…”
Section: Resultsmentioning
confidence: 43%
See 2 more Smart Citations
“…A recent study showed that PhoX is more abundant in the ocean than previously considered (18). We observed that PhoD is even more abundant than PhoX across a wide variety of marine habitats.…”
Section: Resultsmentioning
confidence: 43%
“…The replacement of Zn 2ϩ with Ca 2ϩ could be an important factor in the selection of PhoX and PhoD over PhoA in the ocean. We applied a loose but reliable searching criterion and identified more PhoA and PhoX homologs than previously shown (18). The abundant nature of PhoD genes suggests that they may play an important role in organophosphate hydrolysis in the surface oceans.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Target genes for oligonucleotide probe design were selected based on existing knowledge of gene markers that target microorganism interactions with their environment (for example, Lindell and Post, 2001;Webb et al, 2001;Holtzendorff et al, 2002;Chen et al, 2004;Fuller et al, 2005;Dyhrman and Haley, 2006;Zehr et al, 2007;Orchard et al, 2009;Sebastian and Ammerman, 2009;Kamennaya and Post, 2011;Mosier and Francis, 2011;Paerl et al, 2011). Several genes for hypothetical proteins that were differentially expressed in response to specific stimuli in cultured marine microorganisms were also included (Scanlan et al, 1996;Martiny et al, 2009;Shi et al, 2009;Tetu et al, 2009; et al, 2011).…”
Section: Design Of the Microtools Microarraymentioning
confidence: 99%
“…Alkaline phosphatases (phoA) are thought to be located in the periplasm and are activated by Zn and magnesium, whereas other alkaline phosphatases (phoX, phoD) are activated by calcium ions (Luo et al, 2009). A recent survey of the metagenomic databases concluded that phoX appeared to be more widespread in the ocean than phoA (Sebastian and Ammerman, 2009). There are also other types of alkaline phosphatases in cyanobacteria.…”
Section: Alkaline Phosphatasesmentioning
confidence: 99%